Potret Kekuasaan dan Ketidakadilan dalam Novel Senja di Jakarta Karya Mochtar Lubis: Kajian Poskolonial - Nensilianti; Ridwan; Srikandi Apriliyani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This research aims to find out how the portrait of power and injustice of the government and party officials towards the community contained in the novel by Mochtar Lubis entitled Senja di Jakarta which is set during the liberal democracy period in the 1950s. The method used in this research is descriptive qualitative, which is a research method that explains the content of the facts, the condition of the problems that occur in the novel. This research also uses data processing techniques carried out by reading and interpreting each quotation data found, adjusted based on the theory used. The data obtained is taken from the novel Senja di Jakarta. The research used postcolonial theory. Based on the results of the analysis, two data were found, namely, a portrait of power and injustice contained in the novel involving the government and party officials which caused great misery and impact on society. Senja di Jakarta also tells about the condition of people from various professions and circles and provides an overview of the colonial situation experienced by the community that does not necessarily refer to torture and physical violence as happened in previous colonizations.